Conversor LLC auto-oscilante com retificação síncrona para carregamento de baterias chumbo-ácidas - Daros, Giancarlo Clerici (2022)
This work presents the analysis, development and implementation of a lead-acid battery charger through an LLC resonant converter with variable output power capability and an active MOSFET synchronous rectifier. The half-bridge LLC resonant converter aims achieving low voltage levels and obtaining variable output power for an individual leadacid cell. A variable output power metodology is conceived through a variable current transformer (VCT) considering self-oscilating systems. The VCT impedance changing induces to modifications in the resonant filter equivalent impedance, thus leading to diferent operating points and, consequently, diferent voltage and current gains. Besides, it is desirable obtaining ZVS characteristic for all operating points. Thus, this work presents an active synchronous rectifier, looking for reducing complications that will be caused by the rectification diodes. Once the converter, VCT and synchronous recitifer are designed, simulation results are presented to verify the operation considering all the previous funcionalities. After, experimental results show the circuit behavior considering the aforementioned features.